Relationship Between Salivary pH and Candida albicans Growth in Elderly with Diabetes Mellitus - Putri, Alya Ernita; Qurrohman, Muhammad Taufiq (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Candida albicans is the most dominant Candida species found in the oral cavity, this fungus will turn into a pathogen if there is excessive growth on the oral mucosa which is usually called oral candidiasis. Elderly people with diabetes mellitus have a higher vulnerability due to a weakened immune system that supports the colonization of pathogenic microorganisms. Low pH conditions in saliva can facilitate the growth of Candida albicans fungi, thereby causing pathogenic microorganisms to multiply more rapidly. The purpose of this study was to determine the relationship between salivary acid pH and the growth of Candida albicans fungi in elderly people with diabetes mellitus. The study used an analytical observational design, the sample used in this study were 24 elderly patient respondents with diabetes mellitus. From the results of the study, it can be concluded that there is a significant relationship between salivary acid pH and the growth of Candida albicans fungi in elderly people with diabetes mellitus, which indicates that salivary pH can affect fungal colonization in the oral cavity. Acidic salivary pH conditions have the potential to significantly increase the number of Candida albicans colonies, thereby increasing the risk of oral candidiasis in people with diabetes mellitus.